Adolescents, Obesity, and Road Traffic Accident: Based on Indonesia National Survey - Intan Zainafree; Nadia Syukria; Silfia Addina; Muhamad Zakki Saefurrohim (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Introduction: The percentage of adolescents in Indonesia was 8.8%. Adolescents aged 15 – 20 years were the second highest (79.2%) injured due to road traffic accidents (RTA) with riding motorcycle. This study aimed to analyze the relationship between several variables that were predicted to be the cause of RTA of adolescents aged 15 – 20 years in Indonesia. Methods: This study used a cross sectional design using data obtained from the 2018 Basic Health Research (Riskesdas). The research sample was individuals aged 15-20 years who had experienced an injury. A total of 2,042 people were selected based on injuries due to traffic accidents and not from traffic accidents itself. Variables of gender, rural or urban areas, helmet use habits, suitability of using helmets, smoking status, history of consuming minimal alcohol, emotional mental disorder issues and obesity issues. Bivariate analysis used the chi-square test with a significance level of P-value <0.05 and 95% confidence interval (CI), and multivariate analysis used the Binary Regression Logistic test. Results: The variables of gender, helmet use habit, smoking habit, and obesity issues had a significant relationship with P-value < 0.005 with the incidence of traffic accidents in adolescents in Indonesia. After controlling of other variables, the direction of the positive relationship was shown in the variables of gender and obesity status with PR (95%CI) is 1.394 (1.139-1.706) and 1.551 (1.232-1.952). Conclusion: Road Safety Education for adolescents aged 15-20 years, especially adolescents with obesity needs to be structured and implemented according to the needs of adolescents. KEYWORDS: Road Traffic Accidents, Road Traffic Injury, Obesity, Adolescents, Indonesia